Modul Elektronika Berbasis STEAM (Science, Technology, Engineering, Arts and Mathematics) pada Materi Komponen Listrik Sekolah Dasar Kelas V - Kusumarani, Fatimah; Sarwanto; Sri Marmoah (Jurnal Pendidikan dan Pengajaran, 2024)
The challenge in implementing the independent curriculum is teachers ' readiness to use digital technology for learning. Teachers are required to be able to use technology, but many still need help developing digital media for learning. This research aims to develop a STEAM-based electronic module for class V elementary schools learning electrical components. This type of research uses the 4D development model (Define, Design, Develop, and Disseminate). The research subjects were media experts, learning materials experts, and language experts. The test subjects were five teachers and students. Data collection methods used in this research include interviews, questionnaires and tests. The instrument used to collect data was a questionnaire sheet. The techniques used to analyze data are qualitative descriptive analysis and quantitative and inferential statistics. The results of the research show that there is a significant difference between before and after using STEAM-based electronic modules and after. It was concluded that STEAM-based electronic modules can improve students' higher-order thinking abilities. This research highlights the potential of e-module learning tools, particularly in the context of a STEAM approach, in improving educational outcomes. The implication of this research is that STEAM-based electronic modules can be used in learning.